Premature Professionalisation or Early Engagement? Examining Practise in Football Player Pathways - Sweeney, Liam; Horan, Dan; MacNamara, Áine (Frontiers in Sports and Active Living, 2021)
There is a growing debate, both in the academic and sporting worlds, about the most appropriate pathway for high potential young players in sport. In this regard, there has been a considerable focus on the age of selection into structured talent development pathways and the nature of the experience once players have been recruited. Given the economic and reputational currency associated with developing professional footballers in particular, it is unsurprising that professional football clubs continue to invest significant financial resources into their academy structures. Understandably, this recruitment policy has attracted substantial attention within the media and research community, with ethical concerns arising surrounding the impact early selection may have on the welfare and the experiences of the young players within the pathway. The aim of this perspective article was to critically consider the research underpinning the early engagement practices of football clubs and the extent to which, and how, the pathway can provide players with the most appropriate starting point for their development. This evidence points to the need to look beyond the prevalent ‘early specialization versus diversification’ debate in youth sport towards a consideration of an early engagement perspective that reflects the biopsychosocial influences on talent development and the socio-political environment that influences decisions. We provide practical recommendations focused on the quality of the early engagement experience.